2021
DOI: 10.3390/geosciences11100423
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Historical Land-Use Change on Contemporary Channel Processes, Form, and Restoration

Abstract: Big Harris Creek, North Carolina, possesses a geomorphic history similar to many drainages in the southern Appalachian piedmont, and was used herein as a representative example of the influence of European settlement on contemporary channel form and processes. The integrated use of historical, dendrogeomorphic, stratigraphic, and cartographic data shows that the conversion of land-cover from a mix of natural conditions and small farms to commercial cotton production in the late 1800s and early 1900s led to sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 60 publications
(95 reference statements)
0
18
0
Order By: Relevance
“…The Big Harris Creek Basin, a tributary to the First Broad River, is the site of one of the largest stream restoration projects in North Carolina, a project that encompasses the upper 9.6 km 2 of the basin. Detailed analyses, which included the interpretation of historical, stratigraphic, dendrochronologic, and cartographic data, demonstrated that the geomorphic history of the basin was similar to many other catchments within the southern Appalachian piedmont [30]. Immigration to the area began during the mid-1700s.…”
Section: Study Areamentioning
confidence: 95%
See 4 more Smart Citations
“…The Big Harris Creek Basin, a tributary to the First Broad River, is the site of one of the largest stream restoration projects in North Carolina, a project that encompasses the upper 9.6 km 2 of the basin. Detailed analyses, which included the interpretation of historical, stratigraphic, dendrochronologic, and cartographic data, demonstrated that the geomorphic history of the basin was similar to many other catchments within the southern Appalachian piedmont [30]. Immigration to the area began during the mid-1700s.…”
Section: Study Areamentioning
confidence: 95%
“…Immigration to the area began during the mid-1700s. Most early settlers in the catchment were engaged in general farming practices until after the Civil War (1861-1865) [30]. A typical farm at the time included a combination of free-ranging livestock (mostly pigs), vegetable gardens, and a few fruit trees and/or cornfields.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations